Artistic research and activitism: beyond music, multimedia and visual art - Benetti, Alfonso (2023)
Undine is a mythical figure, a water nymph associated with the female gender – just as water was seen in ancient Greece. Due to her proximity to humans, Undine assumes an identical body figure, however, she does not have a soul. Such torment only ends when the nymph marries a human, which also has consequences: the guarantee of an immortal soul makes their lives shorter. Choreography of shadows: Undine’s Torment is an artwork – the result of an interdisciplinary artistic research project involving music, multimedia and visual art, conducted within the scope of the Xperimus funded project (Experimentation in music in Portuguese culture: History, contexts and practices in the 20th and 21st centuries). Related to the myth of Undine, the objective of the work was to develop an artistic output that, as a result of the interaction between the visual and the sound, would represent the Waters of the Ria de Aveiro (Portugal) by the “feminine” that inhabits it. This objective refers to 1) valuing a territory in preservation – political and ecological activism; and a 2) gender activism: the valorization of the feminine (in Portuguese, “Ria” is the feminine word for the masculine “Rio” - River). The research was based on methodological procedures such as archeology (Foucault), performance-ethnography (Bayley; Canonne), musical collage, musical borrowing, improvisation, extended techniques and experimental methods (Assis 2008). The work was developed within the scope of a creative laboratory, preserving an immersive dialogue between an artist-researcher and a visual artist. In musical terms, the final result consisted of a creation based on resources from the piano, performed/recorded and later explored and mixed through audio programming. In terms of instrumental performance, in addition to the usual use of the piano, the work includes exploratory effects such as arpeggios performed manually on the instrument's strings, wooden blows on the bass strings, and the friction of glass on the instrument's strings - an effect that appears in the work as allusive to Undine's singing. The exploration and sound editing were based on the plot alluding to the myth, focusing on the shadow effect – representative of Undine's movement through the waters of the Ria de Aveiro. The final artistic result interpolates music with multimedia and visual art – mainly through the exploration of audiovisual resources and the arrangement of archaeological artefacts. This presentation includes an exhibition of the final artistic output, a reflection on the procedural aspects and aims related to the artistic research project, and a discussion on activism as a consequence of the ideological impact linked to artistic research.